Inovasi Bisnis Organisasi Melalui Pemanfaatan Sistem Dan Teknologi Informasi - Raisida Salwa; Muhammad Irwan Padli Nasution (Pusat Riset dan Inovasi Nasional, 2024)
In the current era of globalization and digitalization, business innovation is crucial for organizations to maintain and enhance competitiveness. The utilization of Information Systems and Technology (IT) serves as a foundational element for business innovation. This article explores how organizations can implement business innovation through the utilization of IT to achieve a competitive advantage. It delves into the central issues of IT in the business context, discussing the role of IT in supporting business operations and strategies. The study aims to understand the pivotal role of business innovation in organizational success and examines real-world cases where organizations successfully implemented innovation through IT. The challenges and obstacles faced, including data security and implementation costs, are addressed, and effective strategies to overcome these challenges are proposed. The conclusion highlights the strategic significance of investing in business innovation supported by IT for organizations aiming to stay relevant and sustainable in the ever-evolving global market.